Total energy expenditure in elite open-water swimmers - Sagayama, H.; Mimura, K.; Toguchi, M.; Yasukata, J.; Tanaka, H.; Higaki, Y. (Applied Physiology, Nutrition, and Metabolism, 2019)
This study aimed to examine the total energy expenditure (TEE) and physical activity level (PAL) of elite open-water swimmers. Our study group included 5 world-class competitive open-water swimmers. TEE was measured using the doubly labeled water method for 1 week. The TEE was 4549 ± 1185 kcal/day. The PAL was 3.22 ± 0.46. Our results may provide a reference to optimize energy requirement support.